Sustained release of a thiosemicarbazone from antibacterial electrospun poly(lactic‐co‐glycolic acid) fiber mats. (28th July 2020) - Barani, Hossein; Haseloer, Alexander; Mathur, Sanjay; Klein, Axel
Abstract : Antibacterial fiber mats of poly(lactic‐co‐glycolic acid) (PLGA) were produced in the presence of different amounts of the thiosemicarbazone (TSC) N 4‐( S )‐(1‐phenylethyl)‐2‐(pyridin‐2‐ylmethylene)hydrazine‐1‐carbothioamide (HfpyTSCmB) through electrospinning. Increasing amounts (0, 2.5, 5, and 10 wt%) of TSC in the PLGA spinning solution in 2, 2, 2‐trifluoroethanol (TFE) caused an increase up to 230% in conductivity and up to 27% in viscosity. The morphology of the electrospun fibers was studied using scanning electron microscope (SEM) and showed the formation of uniform, bead free, cylindrical, and smooth fiber mats. Increasing amounts of HfpyTSCmB in the polymer solution resulted also in significant shrinking of the diameter and narrowing of the size distribution of the fibers in line with the increased conductivity of the spinning solutions. Nuclear magnetic resonance (NMR) spectroscopy and thermal methods (DSC and TG/DTA) gave proof for the chemical integrity of HfpyTSCmB in the fiber mats after the electrospinning process. The release profile of HfpyTSCmB from the fibers was examined using UV‐vis absorption spectroscopy. The observed release data during 21 days was fitted to different mathematical models with the best results obtained from the Higuchi release model. The fiber mat samples showed effective antibacterial properties with inhibition zones of 0.5 to 1.5 mm against the Gram‐positive Staphylococcus aureus and the Gram‐negative Escherichia coli .